1
$\begingroup$

Ok so I'm kind of struggling with this: The question is:

"Use mathematical induction to prove that 1*3 + 2*4 + 3*5 + ··· + n(n + 2) ≥ (1/3)(n^3 + 5n) for n≥1"

Okay, so P(1) is true as 1(1+2)=3 and (1/3)(1^3 + 5)=2 Assuming P(k) is true for k≥1 gives:

1*3 + 2*4 + 3*5 + ... + k(k+2) ≥ (1/3)(k^3 + 5k)

And we want to show that P(k+1) is true, that is;

1*3 + 2*4 + 3*5 + ... + (k+1)(k+3) ≥ (1/3)((k+1)^3 + 5(k+1)) (inequality 1)

This is where I'm not sure if I'm thinking along the right lines or not. Surely, by P(k) and the rules for inequalities we get:

(1*3 + 2*4 + 3*5 + ... + k(k+2)) + (k+1)(k+3) ≥ (1/3)(k^3 + 5k) + (k+1)(k+3) (inequality 2)

but the right hand side in this inequality does not equal (1/3)((k+1)^3 + 5(k+1)) which is what I am trying to show. There's obviously a flaw in my thinking somewhere so any help would be greatly appreciated. Thanks

Edit: As far as I understand it the right hand side of inequality 1 should equal the right hand side of inequality 2 but this isn't the case when expanded

$\endgroup$
  • 2
    $\begingroup$ because they are not equal. you should show that one is greater than the other $\endgroup$ – benji Feb 13 '15 at 20:12
  • 1
    $\begingroup$ If your know $x \geq y$ and you find $y \geq z$, then you've established $x \geq z$. You'll find the expansion of the right-hand side of $(2)$ is greater than the right-hand side of $(1)$. So you simply need to show that. $\endgroup$ – Namaste Feb 13 '15 at 20:26
  • $\begingroup$ I don't understand why they wouldn't be equal? I thought that if x>y then (x+a)>(y+a) which is how inequality 2 comes about $\endgroup$ – Michael Feb 13 '15 at 20:37
2
$\begingroup$

Assume that statement is true for number unto k. We need to show that it is true for k+1.

$$ 1*3+...+k(k+2)+(k+1)(k+3)\geq \frac{k^3+5k}{3}+(k+1)(k+3)=\frac{k^3+3k^2+17k+9}{3}\geq\frac{k^3+3k^2+8k+6}{3}=\frac{(k+1)^3+5(k+1)}{3} $$

for last inequality expand both sides and see that

$$ \frac{(k+1)^3+5(k+1)}{3}=\frac{k^3+3k^2+8k+6}{3} $$

and $$ \frac{k^3+5k}{3}+(k+1)(k+3)=\frac{k^3+3k^2+17k+9}{3} $$

put it in original inequation and get the result

$\endgroup$
  • $\begingroup$ I'm not sure how this proves the result? I know the equations are different but surely we're trying to show that the last inequality is the same as the RHS of P(k+1)? I'm confused lol $\endgroup$ – Michael Feb 13 '15 at 20:28
  • $\begingroup$ Just forget the middle part and see far LHS $\geq$ far RHS. Do you see the statement P(k+1)? $\endgroup$ – Harish Feb 13 '15 at 20:32
1
$\begingroup$

Here's the meat of the argument: \begin{align} 1\cdot3+2\cdot 4+\cdots+(k+1)(k+3)&\geq \frac{k^3+5k}{3}+(k+1)(k+3)\tag{ind. hyp.}\\[1em] &= \frac{k^3+5k+3(k^2+4k+3)}{3}\tag{simplify}\\[1em] &= \frac{k^3+3k^2+17k+9}{3}\tag{simplify}\\[1em] &\geq \frac{k^3+3k^2+8k+6}{3}\tag{since $k\geq 1$}\\[1em] &= \frac{(k+1)^3+5(k+1)}{3}. \end{align} The last equality is what you want. The key is in realizing that since $k\geq 1$ you can obtain the desired expression on the right-hand side to show that $$ 1\cdot3+2\cdot 4+\cdots+(k+1)(k+3) \geq\frac{(k+1)^3+5(k+1)}{3}. $$

$\endgroup$
  • $\begingroup$ ahhh I see now lol. Thanks for the explanation! $\endgroup$ – Michael Feb 13 '15 at 20:41
  • $\begingroup$ @Michael You're welcome 8^) $\endgroup$ – Daniel W. Farlow Feb 13 '15 at 20:42

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.